Perlindungan Hukum bagi Atlet terhadap Pemutusan Hubungan Kerja Sepihak Pada Proses Pengambilalihan Perseroan Terbatas - Mochammad Saddam; Emmanuele Devon Febrian; Maximillian Kenas Tarmidi (Notaire, 2026)
The sports industry has experienced significant growth worldwide, including in Indonesia, as reflected by the increasing number of professional athletes and sports clubs operating as Limited Liability Companies. In this context, the protection of athletes’ rights becomes particularly important, especially when corporate restructuring occurs through the takeover of sports clubs. A takeover may significantly affect the legal relationship between athletes and the club, including the risk of unilateral or forced termination of athletes’ employment contracts by the acquiring company. This study aims to analyze the legal implications of a takeover on the employment status of professional athletes and to examine the forms of legal protection available to athletes, particularly regarding the fulfillment of their economic and social rights following a takeover. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that although a takeover is legally recognized under corporate law, it does not eliminate the company’s obligation to honor existing contractual commitments with athletes. Based on the principle of pacta sunt servanda, contractual rights and obligations remain binding on the parties. Consequently, the unilateral termination of an athlete’s contract without proper legal grounds or adequate compensation constitutes a breach of contract and is inconsistent with the worker protection principles embodied in Indonesian labor regulations. Athletes who suffer losses due to such actions are entitled to seek legal remedies through civil dispute resolution mechanisms or specialized dispute settlement institutions provided by applicable regulations. Therefore, legal protection for professional athletes in takeover situations must be viewed comprehensively through corporate, employment, and contractual law perspectives to ensure a fair balance between business interests and athletes’ rights.